Why are women dying in India’s sterilisation camps? - Pulla, Priyanka (BMJ, 2014)
Far from offering suitable birth control methods to men and women at different points in their lives, India’s programme focuses on female tubectomy carried out in substandard camps, Priyanka Pulla reports